PAINTING THE SKY BLACK. Louis Kahn and the Architectonization of Nature - Sauter, Florian (De Gruyter, 2018)
In 1962, Louis I. Kahn described the design of the Salk Institute as having been developed "out of a respect and understanding of the nature of nature," before adding: "I am becoming increasingly conscious of the architecture of water, the architecture of air, the architecture of light." Attempting to poetically unveil the world through the conscious architectonization of nature, the deliberations presented in this book interpret the American architect's buildings as the result of a Stoic pursuit to comprehend the lawfulness of the natural world, scrutinize his endeavor to set spatial compositions into analogy with organisms' principles of growth and form, illustrate his growing awareness to shape space in reciprocity with environmental forces, and acknowledge his eventual willingness to make the surrounding landscape and cosmos an integrated part of the architectural project. Furthermore, Kahn's highly ambiguous epistemology with regard to man's position within and beyond nature is being discussed - ultimately promoting an ecologically sound down to earth approach, which takes into account the impulse of the primitive and elemental. Aspiring for an eternal expression, the manifestation of the world of the human spirit was for Kahn - one of the most legendary and original architects of the 20th century - only possible within the larger order of the universe, whereas the same transcendent, creative joy pervaded both.